The Effect Of Leverage, Independent Commissioners, and Audit Fees On Financial Statement Integrity With Audit Quality As Moderating Variable (Empirical Study on LQ45 Companies Listed on the Indonesia Stock Exchange in 2019 - 2023) - Bobby Pratama; Fardinant Adhitama; Asfeni Nurullah (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2025)
This research has the main objective to provide special strategies that can be used to increase coffee sales, especially Beanspot. Various data shows that current coffee sales continue to increase, so it is very interesting to research what factors must be met to win the competition. The research method used is descriptive qualitative with data collection through interviews, observation and documentation studies. By carrying out internal analysis consisting of 11 factors and external analysis consisting of 9 factors, the IFAS = 3,349 and EFAS = 3,262 were obtained. In the SWOT diagram, Beanspot is in quadrant III where the most appropriate strategy for Beanspot is stability / turn around or changing tactics. The main suggestion resulting from this research for companies is to focus more on improving the company's internal resources, especially human resources, so that when added to its strengths such as strong networks and competitive prices, Beanspot can dominate the market.